Smoke [large type] - Ide, Joe (Ide, Joe. IQ novel, 2021)
"Isaiah Quintabe is no longer IQ, the genius of East Long Beach; instead, he's a man on the road and on the run, hiding in a small Northern California town when his room is broken into by a desperate young man on the trail of the state's most prolific serial killer. His old partner, Juanell Dodson, must go straight or lose his wife and child. His devil's bargain? An internship at an LA advertising agency, where it turns out the rules of the street have simply been dressed in business casual, but where the aging company's fortunes may well rest on their ability to attract a younger demographic. Dodson--"the hustler's hustler"--just may be the right man for the job."--page 4 of cover